The responses of taxable income induced by tax cuts: Empirical evidence from the German taxpayer panel - Peter Gottfried; Daniela Witczak (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
The elasticity of taxable income has gained increasing attention as a fiscal policy parameter. This paper provides empirical evidence for Germany and adds to the relatively small body of literature for European countries. We use a large new panel data set to analyze the taxable income response to tax rate changes in 2004 which were part of an extensive reform programme in Germany at the beginning of this century. We find an average elasticity of approximately 0.6. Separately estimated income effects however are mostly small or insignificant. The results vary when dividing taxpayers by income type and group.
Keywords: H24; H31; 330; elasticity of taxable income; tax reform; net-of-tax rate; Einkommensteuertarif; Steuerwirkung; Einkommenselastizität; Schätzung; Deutschland